Validity and reliability analysis of a socioscientific issues-based critical thinking self-assessment instrument using the Rasch model - Y. Yokhebed; Rexy Maulana Dwi Karmadi; Luvia Ranggi Nastiti (University of Muhammadiyah Malang, 2025)
Although self-assessment in critical thinking is thought to help students recognise their strengths and weaknesses, the reliability and validity of the assessment tool is still questionable, so a more objective evaluation is needed. Objective of this investigation is to assess the self-assessment tools in evaluating students' critical thinking abilities in relation to socioscientific topics. The instrument was tested on 202 respondents from five high schools in the Bengkayang district. The study employs the Rasch model as implemented in Winstep version 4.5.2. It includes 12 statements that represent six critical thinking skills and six sub-skills based on Facione's definition of critical thinking. The results indicate that the instrument has been validated through item match analysis, and its differentiating power value demonstrates that the test is functioning effectively. Additionally, the instrument's reliability is confirmed by its Cronbach's alpha value, which meets the adequate criterion, as well as its item reliability, indicating that the item quality indicators are at an excellent level. Therefore, future empirical investigations can utilize the self-assessment tool to evaluate students' critical thinking abilities in relation to socioscientific issues.